Battling Nelson, the Durable Dane World Lightweight Champion, 1882-1954 - Baker, Mark Allen (McFarland & Company, Inc., Publishers, 2017)
"This book tells the story of a ring legend whose endurance was second to none and whose trilogy with Joe Gans is one of the great rivalries in sports history"...
Includes bibliographical references and index
Keywords: Nelson, Oscar -- 1882-1954; Geschichte 1882-1954; Geschichte; Boxers (Sports) -- Denmark -- Biography; Boxing -- United States -- History; Boxen; Gewichtsklasse; leicht; Dänemark; USA; Biografie